Architecting AI solutions on Salesforce : design powerful and accurate AI-driven state-of-the-art solutions tailor-made for modern business demands /: design powerful and accurate AI-driven state-of-the-art solutions tailor-made for modern business demands. (2021) - Malmqvist, Lars
No abstract available